Elucidating the photoprotection mechanism of eumelanin monomers - Ghosh, Paulami; Ghosha, Debashree (Journal of Physical Chemistry B, 2017)
Eumelanin, the functional polymer in human skin, forms a heterogeneous layered structure intrinsic to its broadband monotonic spectra. The inherent structural heterogeneity of eumelanin makes the photoprocesses very complex and diverse in nature. Due to this diversity, a complete mechanistic picture of these photoprocesses, essential to understanding the photoprotective properties, has been missing to date. In this study, we recreate the potential energy surfaces of the low-lying excited states of the multiple monomeric forms of eumelanin constituents that play a prominent role in either photoprotection or photodamage pathways. Our results indicate a diverse set of pathways for the photoexcited species to relax back to the ground state, that depends on the specific monomeric form. Furthermore, the excited state reaction channels show the scope of extensive interconversion between the different monomers and therefore, we propose that the heterogeneity of eumelanin is key to its photoprotection capability.

Nature of selenium hydrogen bonding: gas phase spectroscopy and quantum chemistry calculations - Mishra, Kamal K.; Singh, Santosh K.; Ghosh, Paulami; Ghosh, Debashree; Das, Aloke (Physical chemistry Chemical physics, 2017)
<div class="block-record-info" style="margin: 0px 22px 22px; list-style: none; padding: 0px; line-height: 20px; font-size: 13px; color: rgb(51, 51, 51); font-family: arial, helvetica, sans-serif; background-color: rgb(248, 248, 248);"> Subsequent to the recent re-definition of hydrogen bonding by the IUPAC committee, there has been a growing search for finding the presence of this ever interesting non-covalent interaction between a hydrogen atom in an X-H group and any other atom in the periodic table. In recent gas phase experiments, it has been observed that hydrogen bonding interactions involving S and Se are of similar strength to those with an O atom. However, there is no clear explanation for the unusual strength of this interaction in the case of hydrogen bond acceptors which are not conventional electronegative atoms. In this work, we have explored the nature of Se hydrogen bonding by studying indole...dimethyl selenide (indmse) and phenol...dimethyl selenide (phdmse) complexes using gas phase IR spectroscopy and quantum chemistry calculations. We have found through various energy decomposition analysis (EDA) methods and natural bond orbital (NBO) calculations that, along with electrostatics and polarization, charge transfer interactions are important to understand Se/S hydrogen bonding and there is a delicate balance between the various interactions that plays the crucial role rather than a single component of the interaction energy. An in-depth understanding of this type of non-covalent interaction has immense significance in biology as amino acids containing S and Se are widely present in proteins and hence hydrogen bonding interactions involving S and Se atoms contribute to the folding of proteins.
Keywords: Center-Dot-O; Clusters; Co-Ordination; Complexes; intermolecular interactions; Proteins; Replacement; spectra; Strength; Sulfur